Fault detection and diagnosis of large-scale HVAC systems in buildings using data-driven methods: A comprehensive review - Mirnaghi, Maryam Sadat; Haghighat, Fariborz (Energy and buildings, 2020)
•Reviewing limitations of previous data-mining based FDD methods on HVAC systems.•Knowledge-based and model-based systems have limitations in complicated FDD process.•In FDD in large-scale HVAC systems, driven methods are superior to other methods.•Hybrid methods have greatpotential in finding naïve faults in FDD process.•Developed hybrid methods can overcome delays, and get less false and missed alarms. Abnormal operation of HVAC systems can result in an increase in energy usage as well as poor indoor air quality, thermal discomfort, and low productivity. Building automated systems (BAS) collects a massive amount of data related to the operation of each component of HVAC systems. Although BAS has been implemented in many buildings over the past decade, the collected data have not been analyzed thoroughly. Some studies have relied on data-mining methods to predict, detect, and diagnose faults in HVAC systems. This paper critically reviews the existing literature and identifies the research gaps in data-driven data mining fault detection and diagnosis (FDD) methods studies on HVAC systems. In this review, data-driven based FDD methods are classified into three classes, namely supervised, unsupervised, and hybrid-learning methods. The hybrid approaches are introduced as the preferred methods among the existing approaches to be used in online FDD processes. Furthermore, some components of HVAC systems and their potential faults are discussed in detail. The outcome of this review shows that data-driven based approaches are more promising for the FDD process of large-scale HVAC systems than model-based and knowledge-based ones. Moreover, an optimal approach could involve both supervised and unsupervised learning (hybrid methods).